Ultraviolet-stimulated photocatalysis of crystal violet using (Gd(2-x)La(x)Zr(2-x)Sn(x)O7) pyrochlore nanoparticles - Mohamed Abdelbaky; Amr Mohamed Abdelghany; Ahmed Hamza Oraby; Mohamed M. Rashad (Applied Water Science)
Abstract The development of improved photocatalytic materials for the effective destruction of crystal violet under UV irradiation has been a crucial focus in water purification research. The advanced oxidation process, specifically the Fenton-like process, proved an excellent efficiency with the degradation of organic dyes such as crystal violet. Gd(2-x)La(x)Zr(2-x)Sn(x)O7 pyrochlore nanopowder is successfully prepared by sol–gel auto-combustion method where (x = 0.1, 0.2, 0.3, and 0.5). Various characterization techniques have been utilized for studying the prepared nanopowder, such as Fourier transform infrared (FTIR), X-ray diffraction (XRD), ultraviolet–visible (UV–visible), and transmission electron microscope (TEM). Moreover, to ensure the efficiency of the photocatalysis process, unknown concentrations were determined using the visible spectrophotometer. At the completion of the purifying process (90 min), photocatalysis processes containing pyrochlore (Gd(2-x)La(x)Zr(2-x)Sn(x)O7) and H2O2 or H2O2 alone are identical; nevertheless, the first one has significant benefits throughout the purification period based on C/C0 values.